Prospects and obstacles of digital quality management in Saudi Arabia universities. A systematic literature review from the Last Decade - Saad Aziz Al-Otaibi; Hasna Balaj Albaroudi (Cogent Business & Management, 2023)
Higher education institutions throughout the world are facing difficulties from political, economic, and technical causes, demanding the adoption of innovative management techniques and organisational structures to preserve their places in the global market. In this environment, digitization has emerged as a vital instrument for boosting educational quality in institutions throughout the world. A relatively new idea, digital quality management, has gained traction in higher education institutions. The purpose of this study is to investigate the role of digital quality management in supporting exceptional development in Saudi Arabian institutions through the digital transformation process. The research technique adhered to the PRISMA 2020 statement, resulting in the selection of 36 papers on digital quality management. There were three key data classifications that developed, including education and learning, digital transformation, and quality management studies. The evaluation discovered significant weaknesses in higher education institutions' quality management systems for digital development. Existing research has mostly focused on traditional methodologies for evaluating quality management, such as lean six sigma, comprehensive quality management, and quality management systems used by Saudi institutions. Establishing and maintaining high-quality assurance and management in higher education is critical for long-term advancement since continuous quality review is critical to success. The findings of this study will help higher education institutions identify their digital quality management strengths and areas for improvement, encouraging academics to reevaluate quality objectives and digital learning management strategies in order to improve overall learning quality. Finally, via the process of digital transformation, digital quality management provides an effective outlet for Saudi Arabian institutions to build long-term competitive advantages and promote outstanding development.
Keywords: 650; digital learning; digitalization; quality management; quality management system; Saudi Arabia; universities